Corn supplementation on milk urea nitrogen content of dairy cows grazing on temperate annual pasture - Dall-Orsoletta,Aline Cristina (2020)
ABSTRACT: The excretion of urinary nitrogen (N), one of the most important environmental contaminants from livestock systems, is highly correlated with milk urea N content. The objective of this research was to evaluate the use of different types of corn supplementation on milk urea N in grazing dairy cows. Twelve Holstein × Jersey lactating dairy cows were divided into six uniform groups according to milk production, lactation stage and live weight. Treatments were compared according to a 3 × 3 replicated Latin square experimental design, with three periods of seventeen days (twelve days to adaptation and five to measurements). The experimental treatments were exclusively grazing (G); grazing + supplementation with 4.2 kg DM of corn silage (CS) and grazing + supplementation with 3.2 kg DM of ground corn (GC). The pasture used was annual ryegrass (Lolium multiflorum L.) and white oats (Avena sativa L.). The milk protein production increased 65 g/day in the GC treatment group compared to the G and CS groups. The supplemented dairy cows showed lower milk urea N (-2.8 mg/dL) than unsupplemented cows, but the N utilization efficiency (g N output in milk/ g N intake) did not change between treatments (average = 0.26). Additionally, there was a relationship between milk and plasma urea nitrogen concentrations (R2 = 0.64). In conclusion, for dairy cows grazing annual temperate pastures, corn ground supplementation increased milk protein production and reduced the excretion of milk urea N, whereas corn silage reduced the excretion of milk urea N without affecting milk protein production.